Adaptive Array Antenna Using On-Off and CMA Algorithms for Microwave RFID Readers - Tanawut TANTISOPHARAK; Akkarat BOONPOONGA; Chuwong PHONGCHAROENPANICH; Phaophak SIRISUK; Monai KRAIRIKSH (My University, 2011)
This paper proposes an adaptive antenna using a combination of on-off and CMA algorithms. With the proposed technique, the on-off algorithm is first employed to search for a desired signal direction in which maximum received power is achieved. Then, interference is suppressed by performing CMA. Simulations are conducted according to the potential application of the proposed adaptive antenna. The simulation results show the SINR improvement implying that the proposed adaptive antenna can be applied to microwave RFID systems in order to resolve reader collision. Furthermore, the proposed adaptive antenna is implemented and then experimented. The experimental results verify that the proposed adaptive antenna can reduce interference resulting in the collision problem.
Keywords: Adaptive beamformer; Adaptive algorithm; RFID technology advancements